Characterization of the Opp Peptide Transporter of Corynebacterium pseudotuberculosis and Its Role in Virulence and Pathogenicity - Moraes, Pablo M. R. O. (Hindawi Publishing Corporation, 2014)
Despite the economic importance of caseous lymphadenitis (CLA), a chronic disease caused by Corynebacterium pseudotuberculosis, few genes related to the virulence of its etiologic agent have been characterized. The oligopeptide permease (Opp) transporters are located in the plasma membrane and have functions generally related to the uptake of peptides from the extracellular environment. These peptide transporters, in addition to having an important role in cell nutrition, also participate in the regulation of various processes involving intercellular signaling, including the control of the expression of virulence genes in pathogenic bacteria. To study the role of Opp in C. pseudotuberculosis, an OppD deficient strain was constructed via simple crossover with a nonreplicative plasmid carrying part of the oppD gene sequence. As occurred to the wild-type, the ΔoppD strain showed impaired growth when exposed to the toxic glutathione peptide (GSH), indicating two possible scenarios: (i) that this component can be internalized by the bacterium through an Opp-independent pathway or (ii) that there is toxicity while the peptide is extracellular. Additionally, the ΔoppD mutant presented a reduced ability to adhere to and infect macrophages compared to the wild-type, although both strains exhibit the same potential to colonize spleens and cause injury and death to infected mice.